Different feeding preferences for macronutrients across seasons and sites indicate temporal and spatial nutrient limitation in the black bog ant - Bezděčková, Klára; Bezděčka, Pavel; Fibich, Pavel; Klimeš, Petr (Oecologia, 2024)
How the resource use by consumers vary in different environments and time scales is one of the fundamental ecological questions. Replicated field studies are rare, however; so the extent to which nutrient use varies and why is uncertain. We studied an endangered tyrphobiotic species, the black bog ant (Formica picea), and its feeding preferences in temperate peatlands. We conducted a baiting experiment at three different sites with high nest densities, repeated over three years and three periods of growing season. Preferences for three main macronutrients (carbohydrates, proteins and lipids) were assessed. We hypothesised that if nutrient limitation plays a role, ants will have an increased need for proteins and lipids in early seasons when brood is raised, while carbohydrates use will increase in late seasons. We also expected that site identity would influence nutrient preferences, but not year. Our results supported the nutrient limitation hypothesis for proteins that were consumed more in the early season. In contrast, preference for carbohydrates was rather high and did not increase consistently through season. Although the occupancy of lipid baits was low overall, it increased at colder temperatures, in contrast to carbohydrate and protein baits. Nutrient preferences varied more among sites than years, with the lowest nutrient use observed in a diverse fen-meadow, consistent with the nutrient limitation hypothesis. Year affected ant abundance, but not bait occupancy. Our results suggest that black bog ants flexibly adapt their diet to environmental conditions and that an interplay between nutrient limitation and climate determines their feeding behaviour.
Keywords: živiny; Seasons; Wetlands; Feeding Behavior; mokřady; preference v jídle; Field experiment; zvířata; Ants; Nutrients; Food Preferences; Food resources; roční období; stravovací zvyklosti; Temporal variance; Nutrition; Formicidae; Animals